Permainan matematika kognitif menggunakan integrasi pygame dan pygzero di SMA Negeri Rongga Bandung Barat - Setiawan, Wahyu; Martin Bernard; M. Afrilianto (Abdimas Siliwangi, 2025)
Cognitive mathematics games are an innovative tool to enhance student engagement by visualizing abstract mathematical concepts, which are often perceived as difficult, into something easier and more enjoyable. The goal is to help students realize that mathematics is not something to be feared, but rather a challenge that they can solve on their own. By using cognitive mathematics games, the interaction between teachers and students in the classroom becomes more conducive and enjoyable. This media is designed using Pygame and PygZero, which are game development applications in Python programming, making it easier for anyone — including educators, teachers, and lecturers — to create the media. The media was introduced to students of SMA Negeri Rongga in West Bandung as a trial in the development of cognitive mathematics games, where it served as a motivational tool to stimulate students’ logical thinking processes in solving problems through gameplay. Examples of the games introduced to students include the Tower of Hanoi and Frog Jump, both of which are linked to mathematical concepts as the final solution. At the end of the community service activity, students gave positive feedback on the use of the cognitive game media